POTRET PENDIDIKAN DI INDONESIA DAN KESIAPANNYA DALAM MENGHADAPI MASYARAKAT EKONOMI ASIA (MEA) - Widodo, Heri (IAIN Ponorogo, 2015)
Abstracts: Education determines the progress of a nation to be a prosperous country. With education, the pride and civilization of a nation is easily realized. This paper is a small portrait of educational system and educational quality in Indonesia; quality of education is directly correlated to the quality of the graduated in Indonesia. Human resources in Indonesia are deeply affected by quality of education in Indonesia. The fact found that only the qualified human resources can be absorbed in work places. In line with the global live, Indonesians are parts of Asia community and world community, therefore, Indonesians are required to move on following requirement of world community. To cope the existence of âMEAâchanges on education paradigm and making wisdom decisions must be done appropriately that Indonesians can be actively involved in âMEAâ and they are not merely the objects of other Asia Countries. Â Ø©ÙÙØ§ÙÙ Ø§ Ø©Ø¯Ù ÙÙØ¬Ø§ Ø©ÙØ¨ØªØ±ÙØ§Ø¨Ù .Ø§ÙÙØ¯Ù Ø§Ø¹Ù ØªÙ Ø¬ ÙÙÙÙ ÙÙØ¥ ÙÙØµÙÙÙ Ø¨Ø¹Ø´ÙØ§ Ø±Ù ÙØ·ØªÙ Ù ÙÙÙ ÙÙÙØ¹Øª ÙÙ Ø§Ø³Ø§ÙÙÙ Ø©ÙØ¨ØªØ±ÙØ§ ØªÙØ§ÙÂ Ù Ø§Ø¸Ù ÙØ¹ Ø©ÙØ±ØºØµ Ø©Ø±ÙØµ Ø¶Ø±Ø¹ Ø©ÙØ§ÙÙÙ Ø§ ÙØ°Ù ØªÙÙØ§Ø .Ø©Ù Ù Ø¯ÙØªÙ Ø©Ø±Ø§Ø¶Ø Ø§Ø° Ø§ÙÙ Ø±Ù Ø§Ø¨Ø¹Ø´ Ø¨Ø¹Ø´ÙØ§ ÙÙÙ ØªØ§ÙÙÙ Ø£ ÙÙØªØÂ ÙÙØ¬Ù Ø±ÙØ®Ø§ Ø©Ø¯ÙØ¬Ù ØÙÙÙØ¬Ù Ø±ÙØ®Ø§ Ø©Ø¯ÙØ¬ ÙÙØªØ³Ù ÙÙØ¹ Ø©Ø±Ø´Ø§Ø¨Ù Ø±Ø«Ø¤Øª Ø©ÙØ¨ØªØ±ÙØ§ Ø©Ø¯ÙØ¬ ÙÙØ£ ØØ§ÙØ³ÙÙÙØ¯ÙØ¥ ÙÙ Ø§ÙØªØ¯ÙØ¬Ù Ø©ÙØ¨ØªØ±ÙØ§Â .ÙÙ Ø¹ÙØ§ ÙÙØ¯Ø§ÙÙ Ø§ÙÙÙØ¥ Ø¬Ø§ØªØªØ ØªÙÙØ§ ÙÙ Ø©Ø¯Ù ÙÙØ¬Ø§ Ø©ÙÙØ§Ø³ÙÙØ¥Ø§ Ø¯Ø±Ø§ÙÙÙ Ø§Ù .Ø§ÙØ³ÙÙÙØ¯ÙØ¥ ÙØ¯Ù Ø©ÙÙØ§Ø³ÙÙØ¥Ø§ Ø¯Ø±Ø§ÙÙÙ Ø§ Ø©ÙØ¹ÙÙ ÙÙ Ø±Ù Ø«Ø¤ØªÂ Ø§Ø°ÙØ¨ .ÙÙ Ø§Ø¹ÙØ§ ÙÙ ØªØ§Ø¹Ù ØªÙÙ Ø¬Ø§ ÙÙ Ø¶Ø¹Ø¨Ù ØØ§ÙØ³Ø¢ Ø¹Ù ØªÙ Ø¬ ÙÙ Ø¶Ø¹Ø¨ Ø§ÙØ³ÙÙÙØ¯ÙØ¥ ÙØ¥Ù Ø©ÙÙ ÙØ¹ÙØ§ Ø±ØµØ¹ ÙÙ Ø©Ø§ÙÙØØ§ Ø¨ÙØ§Ø¬ ÙÙÙÂ ÙØ¯Ø§ØµØªÙÙØ¥Ø§ Ø¹Ù ØªÙÙ Ø¬Ø§ Ø¯ÙØ¬ÙØ¨Ù .Ø±ØµØ§Ø¹ÙÙ Ø§ ÙÙÙ Ø§Ø¹ÙØ§ Ø¹Ù ØªÙÙ Ø¬Ø§ ØªØ§ÙØ¶ØªÙÙ Ø©Ø±ÙØ§Ø³Ù Â Ù ÙØ³ÙÙÙØ¯ÙÙØ¥Ø§ Ø¨Ø¹Ø´ÙØ§ ÙØ·ÙØ® ÙØ£ Ø¯Ø¨ÙØ§Â ÙÙ Ø¯Ø¨ÙØ§ Ø©Ù ÙÙØØ§Ø¨ Ø±ØµØ¹ÙØ§ ØªØ§ÙØ¶ØªÙÙÙ ÙÙÙÙÙ Ø§ Ø°Ø§ØªØ®Ø§Ù Ø©ÙØ¨ØªØ±ÙØ§ ÙÙ Ø±Ø¸ÙÙØ§ ØªØ§ÙØ¬Ù ØªØ§ÙØ±ÙØºØªÂ Ù ÙØ¥ÙÂ Â ÙÙÙØ³ÙØ¢Ø§Â ÙØ§ÙØ³ÙØ£Ø§ ÙÙ Ø§ÙÙØ³ Ø§ÙØ³ÙÙÙØ¯ÙØ¥ ÙÙÙØª ÙØ§ ÙÙØ£ÙÂ Â ÙÙ ÙØ§ØªØ±Ø´ÙØ§Ø§ ÙÙØ¹ ÙØ³ÙÙÙØ¯ÙÙØ¥Ø§ Ø¨Ø¹Ø´ÙØ§ Ø±Ø¯ÙÙÙ Ø§ÙØ¨ Ù Ø§ÙÙÙØ§Â .ÙÙØ¯ÙØ§ ÙÙ Ø§ÙÙØ±ØºÙ